Traditional uses, phytochemistry, pharmacology, toxicity and clinical application of traditional Chinese medicine Cynoglossum amabile: a review - Fan, Yanxiao; Wang, Miaomiao; Zhang, Qing; Ouyang, Shuqi; Mao, Wenhui; Xu, Congli; Wang, Min; Long, Chunlin (Frontiers in Pharmacology, 2024)
Cynoglossum amabile, a member of the Boraginaceae family, is a well-known traditional Chinese medicine and ethnomedicine known as Daotihu. Despite several studies confirming the presence of bioactive pyrrolizidine alkaloids such as amabiline, ambelline, echinatine, europine, and others in C. amabile, there has been no comprehensive review of its traditional uses, phytochemistry, and pharmacology thus far. This review was conducted by thoroughly examining the literature and analyzing network databases. It covers various aspects of C. amabile, including botanical characteristics, geographical distribution, traditional applications, phytochemistry, pharmacological activities, toxicology, and clinical applications. The results have shown that C. amabile has been traditionally used for medicinal, edible, and ornamental purposes in China for many centuries. The whole plant, root, and leaf of C. amabile are used by different ethnic groups, such as Lisu, Bai, Naxi, Yi, Jinuo, and Han, to treat malaria, hepatitis, dysentery, leucorrhea, tuberculosis cough, fracture, joint dislocation, trauma bleeding, and skin carbuncle abscess. A total of 47 chemical components, including alkaloids (pyrrolizidine alkaloids, PAs), sterols, organic acids, and saccharides, were isolated from C. amabile. Pharmacological studies show that the chemical extracts of C. amabile possess various biological activities, such as anti-inflammatory, anti-tumor, anti-microbial, cardiovascular effects, ganglionic action, and acetylcholinesterase inhibition. However, it is important to note that C. amabile exhibits hepatotoxicity, with its toxicity being linked to its primary PAs components. Although preliminary studies suggest potential applications in the treatment of prostate diseases and alopecia, further research is needed to validate these clinical uses. Our review highlights the traditional uses, phytochemistry, biological activity, toxicity, and clinical applications of C. amabile. It emphasizes the essential guiding role of the indigenous medicinal knowledge system in developing new drugs. Previous studies have shown that the phytochemical and pharmacological characteristics of C. amabile are significantly related to its traditional medicinal practices. C. amabile has excellent market potential and can be further analyzed in terms of phytochemistry, pharmacology, and toxicology, which are critical for its clinical drug safety, quality evaluation, and resource development.